New Meanings for Marketing in a New Millennium Proceedings of the 2001 Academy of Marketing Science (AMS) Annual Conference - Moore, Melissa; Moore, Robert S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Founded in 1971, the Academy of Marketing Science is an international organization dedicated to promoting timely explorations of phenomena related to the science of marketing in theory, research, and practice. Among its services to members and the community at large, the Academy offers conferences, congresses and symposia that attract delegates from around the world. Presentations from these events are published in this Proceedings series, which offers a comprehensive archive of volumes reflecting the evolution of the field. Volumes deliver cutting-edge research and insights, complimenting the Academy’s flagship journals, the Journal of the Academy of Marketing Science (JAMS) and AMS Review. Volumes are edited by leading scholars and practitioners across a wide range of subject areas in marketing science. This volume includes the full proceedings from the 2001 Academy of Marketing Science (AMS) Annual Conference held in San Diego, California, entitled New Meaning for Marketing in a New Millennium.
Marketing Education -- Teenage Purchasing Behavior -- Gaining an Edge in Marketing Strategy -- Exploring Retail Customer Behaviors -- Marketplace Behaviors -- Contemporary Issues in Channel Management -- Topics in Advertising Research -- Emerging Perspectives in Environmental Marketing -- Identity and Consumer Behavior -- Pricing Issues for the 21st Century -- Branding and TV Advertising -- Advertising and Promotion -- Current Issues in Marketing Ethics Research: Customer and Company Strategic Issues -- Conflict and Collaboration: Greenpeace and the Corporate World -- Multicultural Purchasing Behavior -- Consumer Behavior, Retailing, and the Internet -- Consumer Decision-Making Processes -- Marketing Management -- Fine tuning Retailer-Supplier Interactions -- Branding and Perception -- Export Marketing -- Perspectives on Salesperson Effectiveness and Commitment -- Consumer Behavior Theory -- Marketing Issues for the Future -- Current Issues in Marketing Ethics Research: International Dimensions -- Business-to-Business Marketing Trends -- Outstanding Marketing Teacher Program -- Current Topics in Services -- Emerging Issues in Internet Marketing and Consumer Behavior -- Contemporary Issues in Sports Marketing -- Research Methods -- Current Issues in Modeling and Measurement -- Influences on Service Customers’ Intentions: The Physical Environment, Satisfaction, and Value.
Keywords: Marketing; Leadership; Sales management; Marketing; Business Strategy/Leadership.; Sales/Distribution.